The Narrative Repatriation of Blessed Kateri Tekakwitha - Holmes, Paula Elizabeth (Anthropologica, 2022)
Blessed Kateri Tekakwitha, a 17th-century Mohawk convert, is one miracle shy of becoming the Catholic Church’s first Native American saint. Contemporary devotion to her is widespread among diverse Native American communities, and she has become the symbolic figurehead of indigenous Catholicism. This article explores the repatriation of Kateri through narratives, as told by her Pueblo women devotees. I suggest that in the women’s counterhagiographical discourses, Kateri is translated from a historically silent figure, bordered by colonial Jesuit categories, into a multivalent intertribal Catholic symbol—a reclaimed Indian saint of creative and heroic character. In my discussion of ethnotheology of sainthood, I examine divergent understandings of Indian identity, Catholic community and the nature of sanctity. I trace the multiple voices which tell Kateri’s lives—from the standardized colonial account to contemporary devotees’ rescripting of and experiences with "their saint."